Modeling the legal field of formation of socially responsible conduct among pharmacy specialists - N. O. Tkachenko; В. Р. Hromovyk (Zaporozhye State Medical University, 2018)
Observation of legal and legislative standards of the company activities is the fundamental principle of social responsibility (SR). The results of the literature analysis show the lack of fundamental research of regulatory and legal support of formation of socially responsible conduct of pharmacists (SRCPh). AIM: modeling the legal framework and determining the completeness and content of the current regulatory and legal framework on formation of a system of SRCPh throughout the professional lifespan development. Materials and methods. The materials of the study were national and international regulatory legal acts, regulating SR, the activities of pharmaceutical organizations (PhO) and getting a pharmaceutical education. During the work, such methods as searching information, systematization, content analysis, comparison and generalization were used. During the investigation, we summarized the legal framework that in various aspects forms the socially responsible conduct of the pharmacists throughout the lifespan professional development; and a model of the legal field of this process was formed. A content analysis of this regulatory framework in aspect of responsibility of the PhO and pharmacists with a description of the problem legal questions in the context of SR was carried out. In this article, attention is paid to the basic level of the legal field, within which general principles of social relations are formed in all spheres of the economy. Conclusions. We have formed a model of the legal field formation of a SRCPh system throughout the professional lifespan development. The model is a complex, multilevel system. The regulatory framework in the model is distributed according to two criteria (hierarchical and regulating relations in the system of socially responsible conduct of the pharmacists) and includes 27 basic normative legal acts. We have identified problems in the legal field of the basic level of SRCPh formation: the indistinctness of the conceptual-categorical apparatus of social standards and guarantees; contradiction between normative legal acts; unfavorable conditions for small business, created by the Tax Code of Ukraine; the neglect of legal norms, the determination of a priority exclusively by receiving a profit, ignoring the PhO and pharmacists moral and ethical principles; inadequate level of political and legal culture in the society; the rejection of the law rule by the political elite and the interpretation of legal norms in their favor; passive behavior of public organizations in the pharmaceutical sector; weak control of the public authorities compliance with standards of current legislature. All specified problems stipulate difficulties in the effective SR implementation.